2019
DOI: 10.1016/j.trim.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD16 expression on NK cells is indicative of antibody-dependent cell-mediated cytotoxicity in chronic-active antibody-mediated rejection

Abstract: Chronic-active antibody mediated rejection (c-aABMR) contributes significantly to late renal allograft failure. The antibodies directed against donor-derived antigens, e.g. anti-HLA antibodies, cause inflammation at the level of the microvascular endothelium. This is characterized by signs of local activation of the complement system and accumulation of immune cells within the capillaries. Non-invasive biomarkers of c-aABMR are currently not available but could be valuable for early detection. We therefore ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Interactions between endothelial‐bound HLA IgG antibodies and myeloid and NK cell FcγRs can facilitate tethering and adhesion of leukocytes. Endothelial cells exposed to HLA antibodies produce cytokines and growth factors that can signal in an autocrine and paracrine manner and promote inflammation 58,59 . Data from in vitro experimental assays indicate that FCGR2A polymorphisms on monocytes govern interactions with distinct HLA IgG subclasses 60 .…”
Section: Attributes Of Hla Antibodiesmentioning
confidence: 99%
“…Interactions between endothelial‐bound HLA IgG antibodies and myeloid and NK cell FcγRs can facilitate tethering and adhesion of leukocytes. Endothelial cells exposed to HLA antibodies produce cytokines and growth factors that can signal in an autocrine and paracrine manner and promote inflammation 58,59 . Data from in vitro experimental assays indicate that FCGR2A polymorphisms on monocytes govern interactions with distinct HLA IgG subclasses 60 .…”
Section: Attributes Of Hla Antibodiesmentioning
confidence: 99%
“…Together with enrichment of other NK-associated transcripts this supported the role of antibody-dependent cellular cytotoxicity (ADCC) in chronic rejecting renal allografts [8][9][10] . In addition, increased expression of the FCGR3A (known as CD16) was noted on circulating NK cells of kidney transplant recipients with a diagnosis of c-aABMR 11 and markers that re ect CD16-dependent activation of circulating NK cells may identify heart transplant recipients at risk for developing cardiac allograft vasculopathy 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of host antibody dependent cell cytotoxicity (ADCC) is known to be conditioned by the capacity of NK effector cells to form conjugates with antibody-coated allogeneic cells, which is in part influenced by the FCGR3A [158V/F] genotype (4547). We and others have recently shown that polymorphic variation in the FCGR3A genes is also likely to affect the pathogenic effects of IgG alloantibodies by controlling the level of the CD16 dependent recipient's immunological cytotoxic responses to allogeneic donor cells exposed to chronic alloantibody threat (35, 4851).…”
Section: Introductionmentioning
confidence: 99%